SEXO E DENSIDADE DE CRIAÇÃO SOBRE O RENDIMENTO DE CARCAÇA E CORTES DE FRANGOS DE CORTE COBB 500® AOS 42 DIAS DE IDADE - SANTOS, João Paulo Gomes; OLIVEIRA, Andréia Fróes Galuci; FERREIRA, Thales Silva; MATTOS, Maria Eduarda da Silva; DOMICIANO, Carlos Henrique Leandro; BASTOS, Augusto Adriano (ANAIS DO ENIC, 2020)
-